LE COURTAGE D’ASSURANCE À L’HEURE DES CHOIX - Ferland, Gaston (Assurances)

(untitled) (HEC Montréal, 1995)
As a result of the profound change in property and casualty insurance customs and the foray of banks into market segments which were previously their exclusive domain, insurers must now reassess their strategy and the ways to best meet the needs of today's insurance consumers. To contend with these new realities, Royal Insurance now offers its brokers three innovative approaches to conduct business: 1) a direct access system (insured/insurer) in the event of a claim; 2) a customer service center where the client deals directly with the insurer; 3) the possibility of giving certain brokers the necessary authority to enable them to oversee and serve their clientele (personal lines and small commercial risks).